Assessment of Upper Basic Education Curriculum Implementation in Banditry Vulnerable Areas of Katsina State - Saulawa, Dr. Abdu Imam; Garba, Munir Abubakar; Masanawa, Dr. Aliyu Sani (Researchparks Publishing, 2023)
The research assessed the implementation of Upper Basic Education Curriculum in vulnerable areas of Katsina state. The population comprised five hundred and seventy six (576) teachers of upper basic school, forty five (45) principals and ninety (90) School Based Management Committee (SBMC) members. Using the research advisors sampling table, the sample of the research stands as two hundred and seventeen (217) teachers, forty four (44) principals and eighty (80) School Based Management Committee members. Five objectives to guide the study were formulated which consequently led to the designing of five research questions. One null hypothesis that centred on curriculum implementation was developed in congruence with the objectives and research questions. A four fingered Likert Scale Questionnaire was developed with twenty (20) items. Mean and standard deviation in the descriptive data were presented. Analysis of variance (ANOVA) was used to test the hypothesis. The findings revealed that the null hypothesis was rejected to infer variation in the respondents opinions in all the five areas of curriculum implementation. It also showed that insecurity constituted a great challenge for curriculum implementation as pupils, teachers could not attend schools regularly. The study recommended among other things proactive measures by security personnel in tackling the challenges, developing appropriate pedagogical strategies of teaching and facilitating good learning environment.